Kuzey Kıbrıs Türk Cumhuriyeti’nde Yaşayan Metabolik Sendromu Olan ve Olmayan Bireylerde Fiziksel Aktivite Düzeyinin Karşılaştırılması - Kazaz, İsmet (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The aim of this research was to determine the physical activity levels of the individuals with Metabolic Syndrome (MetS) diagnosis in TRNC, and compare these with the physical activity levels of the individuals without MetS diagnosis in TRNC. The research group included; the study group that consisted of the volunteers with MetS diagnosis and the control group that consisted of the volunteers who were excluded from the MetS diagnosis criteria. The number of individuals to be involved to the groups in the study was determined by using pawer analiysis. According to the power analisis, the number of individuals to be included in, the examination group: 660 people with MetS (310 Femail, 350 Mail) and the control group: 660 people without MetS (310 Femail, 350 Mail) were determined and then the study was set on. The individuals that were 30-55 years old were included to the study, while those with ortopedic and neurologic disorders, or with conseguential respiratuar problems, or those with major visual, auditory or articulation problems were exdcluded. The sociodemographicattributes and the physical (age, body mass, index) characteristics of the individuals included, were recorded. Pain evaluation (VAS) was used, and to evaluate the life quality of the people involved to the study, Nothingham Health Profile was applied. To determine the physical activity level IPAQ, long was used. CIQ was applied to state the integration of the individuals to the community; and additionally biochemical evaluations were done. SPSS-18 for Windows package programme was used to estimate the data collected; and Ki-square test, T-test, One Way Variance Analysis, Kruskal Wallis Variance Analysis were used as statistical analysis methods. The physical activity level of the people in the MetS group was found significantly lower than the physical activity level of the individuals without MetS as a result of this study. The Study showed that an active lifestyle is a very important criterier in the prevention of MetS. Keywords: Metabolic Syndrome, Physical Activity, Exercise

Öz: Bu çalışmanın amacı; Kuzey Kıbrıs Türk Cumhuriyeti’nde (KKTC) yaşayan metabolik sendrom (MetS) tanısı konmuş bireylerde fiziksel aktivite düzeyini belirleyerek metabolik sendromu olmayan bireylerin fiziksel aktivite düzeyleri ile karşılaştırmaktı. Çalışma, MetS tanısı konmuş gönüllülerden oluşan çalışma grubunu ve MetS tanı kriterleri dışında kalan bireylerden oluşan kontrol grubunu içerdi. Gruplardaki kişi sayısının belirlenmesinde power analizinden faydalanıldı. Power analizi ile birey sayıları 660 MetS’li bireye karşılık (310 kadın, 350 Erkek) 660 kişilik kontrol grubu (310 Kadın, 350 Erkek) olarak belirlendikten sonra çalışma başlatıldı. Çalışmaya, 30-55 yaş aralığında olan bireyler dâhil edilirken, ortopedik ve nörolojik rahatsızlıklara sahip olan, ciddi respiratuar problemleri bulunan, ciddi görme, duyma ve konuşma bozuklukları olan kişiler dâhil edilmedi. Çalışmaya alınan bireylerin Sosyo-Demografik özellikleri, (yaş, eğitim, sigara kullanımı vb) kaydedildi. Bireylerin sağlıkla ilgili yaşam kalitelerini değerlendirmek amacıyla Nothigham Sağlık Profili, depresyon değerlendirmesi için Beck Depresyon Ölçeği, fiziksel aktivite düzeylerinin belirlenmesinde, Uluslar Arası Fiziksel Aktivite Anketi’nin uzun formu kullanıldı, ek olarak biyokimyasal değerlendirmeler yapıldı. Verilerin değerlendirilmesinde SPSS-18 windows paket programı, istatistik analiz yöntemlerinden Ki-Kare testi, t-testi, Tek Yönlü Varyans Analizi, Kruskal Wallis Varyans Analizi kullanıldı. Çalışma sonunda çalışma grubundaki fiziksel aktivite düzeyinin kontrol grubundaki fiziksel aktivite düzeylerine göre çok daha düşük olduğu bulundu. Çalışma grubundaki bireylerin sağlık problemleri kontrol grubuna göre daha çoktu. Çalışma inaktif yaşamın MetS’in oluşmasında önemli etkenlerden biri olarak kabul edilebileceğini ve aktif yaşamın MetS’in oluşmasını engelleme konusunda çok iyi bir başlangıç noktası olabileceğini gösterdi. Anahtar Kelimeler: Metabolik Sendrom, Fiziksel Aktivite, Egzersiz
Fizyoterapi ve Rehabilitasyon Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Fizyoterapi ve Rehabilitasyon Bölümü, 2016. Tez Danışmanı: Yard. Doç. Dr. Ender Angın.
Keywords: Fizyoterapi ve Rehabilitasyon; Metabolik Sendrom; Metabolik Sendrom, Fiziksel Aktivite, Egzersiz; Metabolic Syndrome, Physical Activity, Exercise